Policy and Implementation of Coral Reef Protection in the Face of the Threat of Foreign Ships - Diva Ananta Syofian; Nasyirah Ramadhani Tuasikal; Maria Jessica Lauretta Gunawan; Rachel Christie; Marleen Natania (International Journal Labs, 2023)
Protection of coral reefs in Indonesia from damage caused by foreign ships is an important issue in preserving the maritime environment. is based on Law Number 27 of 2007 and the 1982 Law of the Sea Convention (UNCLOS 1982) which provides the legal basis for protecting marine ecosystems. Steps to increase coral reef protection include setting up zones that limit ship activities, implementing sanctions and strict fines, development of an effective monitoring system, increasing public awareness about the impacts of foreign vessels, and educating fishermen about sustainable fishing practices. International cooperation is an important aspect in dealing with this problem, with collaboration between Indonesia, neighboring countries, and organizations international. This joint effort aims to preserve coral reefs which are a valuable natural resource for Indonesia. The importance of preserving coral reefs as a crucial ecosystem and valuable natural resource for Indonesia must not be ignored. Protection of coral reefs must be a priority in efforts to preserve the environment in Indonesia for a sustainable future.